Visualization of IFNβ production by plasmacytoid versus conventional dendritic cells under specific stimulation conditions in vivo - Scheu, Stefanie (National Academy of Sciences, 2008)
Type I interferons, a protein family of multiple IFNαs and a single IFNβ, initially identified on the basis of their antiviral activities have recently been attributed important roles in bacterial and parasitic infections. To assess the cellular sources of IFNβ, the IFN produced first in most situations, we created an IFNβ reporter-knockin mouse, in which yellow fluorescent protein (YFP) is expressed from a bicistronic mRNA linked by an internal ribosomal entry site to the endogenous IFNβ mRNA. This YFP expression allows spatiotemporal tracking of the initiation of the type I IFN response on a single-cell level. In vitro bone marrow-derived macrophages (BMMΦs) and bone marrow-derived dendritic cells (BMDCs) show IFNβ production from distinct cell subpopulations in response to defined pathogen compounds. A subpopulation of GMCSF-derived BMDCs produced IFNβ after poly(I:C), 3′5′-cytidylylguanosine (CpG), or LPS treatment, whereas Flt3-L-cultured plasmacytoid DCs (pDCs) responded mainly to CpG. After poly(I:C) injection in vivo, IFNβ-producing cells localize to the splenic marginal zone and the lymph node subcapsular sinus. Infection with murine cytomegalovirus (MCMV) induces IFNβ/YFP expression exclusively in few activated pDCs at the T cell/B cell interface of the splenic white pulp. This IFNβ/YFP reporter mouse represents a reliable tool for the visualization and characterization of IFNβ-producing cells in vitro and in vivo.